DIAMETER DAN TEBAL LAPISAN EPITEL TUBULUS SEMINIFERUS SERTA BOBOT TESTIS MENCIT (Mus musculus) SETELAH PEMBERIAN TAUGE KACANG HIJAU (Vigna radiata) - Anindita, Reza; Djaelani, M. Anwar; Mardiati, Siti Muflichatun (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Young mung bean (Vigna radiata) believed as foodstuffs which fertility to defend potent on male. It reliable connected with to be vitamin E antioxidant essence which dominant by the side of other antioxidant as selenium and vitamin C which function in cell to protect from free radical reaction attack on spermatogenesis moment. Spermatogenesis activity on to occur testes inside at to direct seminiferous tubules. This experiment to aim learn tauge kacang hijau supply effect to be seminiferous tubules diameter, seminiferous tubules epithelium thick of layer and testes weight. Trial of animal which used is male rat to amount 10 tail, to divide appoint 2 group, Po as control and P1 is treatment which tauge kacang hijau to receive with oral dose 0,8 g/tail/day as long as 48 day. Observed which variable is seminiferous tubules diameter, seminiferous tubules epithelium thick of layer and testes weight. Acquired which data and then t-test using analyses with 95 % belief of level. Data analyses of result young mung bean supply effect to present not significanceof different to be seminiferous tubules diameter, seminiferous tubules epithelium thick of layer and testes weight treatment the mouse than control (P>0,05). Fact to present that young mung bean treatmen with most dominant vitamin E essence which antioksidant as function impotent spermatogenesis effect reliable in way.